Posted by Anonymous on Tuesday, October 13, 2009 at 7:51pm.
solve the syatem using the substitution method
4x - 5y = - 3
-x + 2y = 3
- algebra 2 - Christiaan, Tuesday, October 13, 2009 at 8:15pm
Using the substitution method means you first find one of the two variables (perhaps in terms of the other variable) and then 'substitute' this result in the other equation. If we apply it on this system we would work as follows:
1) Look at the second equation. You can easily rewrite this to:
x = 2y-3
So now you have x in terms of y
2) You now simple replace every x in the first equation with result you got from the second equation, meaning:
4x - 5y= -3
<=> 4(2y-3) - 5y = -3
<=> (8y - 12) - 5y = -3
<=> 3y = 9
<=> y = 3
3) Now that we have found that y equals 3, we can replace y with 3 in the second equation. We then find that:
x = 2y-3
<=> x = 2*3 - 3
<=> x = 3
So, the solution of this system is:
Answer This Question
More Related Questions
- Algebra 1 - bobpursey, In this problem you helped me with earlier: Solve using ...
- Substitution Method-Plz help - Use the Substitution method to solve the system ...
- Algebra - solve using substitution method: 4x+5y=21 x=48-6y
- Algebra - If 2x + 2y = 20 & 5x - 3y = 15 Solve using the substitution method.
- Algebra Help!! - solve using the substitution method. y= 5 - 3x 4x + y= 7
- Algebra - Solve using substitution method 3x+8y=20 x=24-7y
- Algebra - x-2y=.9 4x-3y=13.1 Solve using the substitution method.
- Algebra - 4x+y=42 6x-5y=50 Solve using the substitution method.
- Algebra - Solve using the substitution method. 0.3x+0.2y=5,0.5x+0.4y=11
- algebra - Solve using the substitution method 6x-3y=18, 6x+3y=-12